2008
DOI: 10.1097/icu.0b013e3282fb7c15
|View full text |Cite
|
Sign up to set email alerts
|

Posterior segment complications after laser-assisted in situ keratomileusis

Abstract: Serious complications after LASIK are infrequent. A dilated fundus examination is very important before LASIK and in every patient whose visual acuity after LASIK is not as good as expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
27
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 33 publications
0
27
0
1
Order By: Relevance
“…42,43 ' Survey of the Literature RRD Much of the discussion concerning retinal detachments after refractive surgery is focused on myopic LASIK. 1,4,44 In 2 of the largest case series to date, the cumulative incidence of RRD after myopic LASIK was found to be 8 of every 10,000 eyes. 45,46 Faghihi et al 46 reported 49 (0.08%) cases of RRD in a series of 59,424 eyes treated with myopic LASIK during a mean follow-up of 31.6 months.…”
Section: ' Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…42,43 ' Survey of the Literature RRD Much of the discussion concerning retinal detachments after refractive surgery is focused on myopic LASIK. 1,4,44 In 2 of the largest case series to date, the cumulative incidence of RRD after myopic LASIK was found to be 8 of every 10,000 eyes. 45,46 Faghihi et al 46 reported 49 (0.08%) cases of RRD in a series of 59,424 eyes treated with myopic LASIK during a mean follow-up of 31.6 months.…”
Section: ' Introductionmentioning
confidence: 97%
“…2,3 The most commonly reported adverse event involving the posterior segment is rhegmatogenous retinal detachment (RRD) after myopic LASIK. 1,4,5 Other retinal pathologies noted after LASIK include choroidal neovascularization (CNV), 5-7 macular hemorrhage, [8][9][10] lacquer crack, 8,11,12 and macular hole (MH). [13][14][15][16] Nearly all of these other complications are, in fact, manifestations of myopic maculopathy.…”
Section: ' Introductionmentioning
confidence: 99%
“…[11][12][13] Posterior segment complications after LASIK using a femtosecond laser for flap preparation also have been reported. 14 Principe et al 15 described a case of postoperative macular hemorrhage, and Hori et al 16 reported on a case of rhegmatogenous retinal detachment. The pathogenesis of posterior segment complications might be related to biomechanical changes either during the application of the suction ring of either the mechanical microkeratome 17 or the femtosecond laser 18 or during the movement of the mechanical microkeratome blade.…”
mentioning
confidence: 98%
“…Refraktiv-chirurgische Eingriffe wie die Laser-in-situ-Keratomileusis (LASIK) und die Laser-gestützte subepitheliale Keratomileusis sind für die Korrektur gering-bis mittelgradiger Myopie heute weit verbreitet [5]. Nach solchen Eingriffen können Komplikationen im hinteren Segment auftreten, die das Sehvermögen bedrohen, darunter makuläre Blutungen, Makulaforamina und rhegmatogene AR [6][7][8][9][10][11][12]. Die Inzidenz der rhegmatogenen AR bei LASIK-Patienten ist laut der Literatur nicht hoch (0,033-0,25%) [9,[13][14][15].…”
unclassified